Transcriptomic analysis unravels the molecular response of Lonicera japonica leaves to chilling stress - Zhang, Meng; Li, Mengxin; Fu, Hongwei; Wang, Kehao; Tian, Xu; Qiu, Renping; Liu, Jinkun; Gao, Shuai; Zhong, Zhuoheng; Yang, Bingxian; Zhang, Lin (Frontiers in Plant Science, 2022)
Lonicera japonica is not only an important resource of traditional Chinese medicine, but also has very high horticultural value. Studies have been performed on the physiological responses of L. japonica leaves to chilling, however, the molecular mechanism underlying the low temperature-induced leaves morphological changes remains unclear. In this study, it has been demonstrated that the ratio of pigments content including anthocyanins, chlorophylls, and carotenoids was significantly altered in response to chilling condition, resulting in the color transformation of leaves from green to purple. Transcriptomic analysis showed there were 10,329 differentially expressed genes (DEGs) co-expressed during chilling stress. DEGs were mainly mapped to secondary metabolism, cell wall, and minor carbohydrate. The upregulated genes (UGs) were mainly enriched in protein metabolism, transport, and signaling, while UGs in secondary metabolism were mainly involved in phenylpropaoids-flavonoids pathway (PFP) and carotenoids pathway (CP). Protein-protein interaction analysis illustrated that 21 interacted genes including CAX3, NHX2, ACA8, and ACA9 were enriched in calcium transport/potassium ion transport. BR biosynthesis pathway related genes and BR insensitive (BRI) were collectively induced by chilling stress. Furthermore, the expression of genes involved in anthocyanins and CPs as well as the content of chlorogenic acid (CGA) and luteoloside were increased in leaves of L. japonica under stress. Taken together, these results indicate that the activation of PFP and CP in leaves of L. japonica under chilling stress, largely attributed to the elevation of calcium homeostasis and stimulation of BR signaling, which then regulated the PFP/CP related transcription factors.